2022
DOI: 10.3390/s22228710
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of and Experimentation with Ground-Penetrating Radar for Real-Time Automatic Detection of Buried Improvised Explosive Devices

Abstract: This paper proposes the implementation of and experimentation with GPR for real-time automatic detection of buried IEDs. GPR, consisting of hardware and software, was implemented. A UWB antenna was designed and implemented, particularly for the operation of the GPR. The experiments were conducted in order to demonstrate the real-time automatic detection of buried IEDs using GPR with an R-CNN algorithm. In the experiments, the GPR was mounted on a pickup truck and a maintenance train in order to find the IEDs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, following the approach of transfer learning in the introduction, it is not of central importance to exactly recreate the overall structure of all possible objects exactly but to present the classifier training data with a certain variance, since machine learning models are typically able to transfer knowledge from one problem to another. For instance, the R-CNN in [14] was trained to classify the hyperbolic pattern of IEDs while being partially trained with hand-drawn hyperbolas. Furthermore, in [12], it was shown that a classifier trained for detection in a certain environment can be transferred to another environment with only a few new training samples.…”
Section: Randomizing Contoursmentioning
confidence: 99%
See 2 more Smart Citations
“…However, following the approach of transfer learning in the introduction, it is not of central importance to exactly recreate the overall structure of all possible objects exactly but to present the classifier training data with a certain variance, since machine learning models are typically able to transfer knowledge from one problem to another. For instance, the R-CNN in [14] was trained to classify the hyperbolic pattern of IEDs while being partially trained with hand-drawn hyperbolas. Furthermore, in [12], it was shown that a classifier trained for detection in a certain environment can be transferred to another environment with only a few new training samples.…”
Section: Randomizing Contoursmentioning
confidence: 99%
“…The use of robots [10] and handheld sensors [11] is particularly important here. In the context of humanitarian demining, a landmine leads to specific spatial reflection signatures in the GPR raw data, as shown in [12][13][14]. A system that applies a similar measurement method is ground-penetrating synthetic aperture radar (GPSAR), which uses a more advanced signal processing procedure following a synthetic aperture radar (SAR) approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground penetrating radar (GPR, georadar) [1][2][3] is widely used in archeology, geology, civil engineering, and security issues [4][5][6]. The problem of GPR radiation directivity plays an important role in planning the measurement paths in rural and urban conditions.…”
Section: Introductionmentioning
confidence: 99%